EMPOWERING ELEMENTARY SCHOOL STUDENTS THROUGH WEBSITE-BASED ENGLISH LEARNING MEDIA - Fauziya, Safira; Muktirrahman, Muktirrahman; Lufnah, Lufnah; Bariroh, Faiqotul; Qomariyah, Mayzalatul; Maksum, Maksum (LPPM Universitas Flores, 2026)
This community service aims to empower elementary school students through the development and implementation of website-based English learning media using a participatory approach. English learning in elementary schools is still dominated by conventional methods that provide limited interactive learning experiences for students. This study employed Participatory Action Research (PAR) combined with the Asset-Based Community Development (ABCD) approach, conducted at Dungkek 1 Public Elementary School for four weeks. The stages included Discovery (local asset mapping), Dream (shared vision formulation), Design (learning website development), and Delivery (implementation and evaluation). A learning website was successfully developed with three main features: theory menu (eight parts of speech and tenses), learning video menu, and interactive games. Teachers gained a new understanding in utilizing digital media, while students showed high enthusiasm with increased active participation in learning. Pre-test and post-test results showed a 65% improvement in English material comprehension. The PAR-ABCD approach proved effective in empowering elementary school students through digital learning media, creating a sense of ownership of the program and ensuring sustainability of learning technology utilization.